2022
DOI: 10.1155/2022/2270384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Optimal Protein Required in Granulated Microdiets for Rockfish (Sebastes schlegeli) Larvae

Abstract: Protein is an essential nutrient that supports fish growth, and the inadequacy in formulating their diets with an optimum protein level can deteriorate their growth performance. The protein requirement in granulated microdiets was estimated for rockfish (Sebastes schlegeli) larvae. Five granulated microdiets (CP42, CP46, CP50, CP54, and CP58) containing 42% to 58% crude protein levels with a 4% increment at a constant gross energy level (18.4 kJ/g diets) were prepared. The formulated microdiets were also compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Many fish have a high demand for proline. In order to attain the highest growth, enough proline must be obtained from the diet, so it is often classified as a conditionally essential amino acid or functional amino acid for fish [ 85 ]. L-Glutamic-gamma-semialdehyde was positively associated with Bacteroides , as Bacteroides increase.…”
Section: Discussionmentioning
confidence: 99%
“…Many fish have a high demand for proline. In order to attain the highest growth, enough proline must be obtained from the diet, so it is often classified as a conditionally essential amino acid or functional amino acid for fish [ 85 ]. L-Glutamic-gamma-semialdehyde was positively associated with Bacteroides , as Bacteroides increase.…”
Section: Discussionmentioning
confidence: 99%
“…7 Vitamin premix (mg/kg or IU/kg diet): vitamin A 7,500.00 IU, vitamin D 1,500.00 IU, vitamin E 60.00 mg, vitamin K3 18.00 mg, vitamin B1 12.00 mg; vitamin B2 12.00 mg, vitamin B12 0.10 mg, pantothenate acid 48.00 mg, niacin 90.00 mg, folic acid 3.70 mg, D-biotin 0.20 mg, pyridoxine 60.00 mg, and vitamin C 310.00 mg. 8 Mineral premix (mg/kg diet): Zn 35.00 mg, Mn 21.00 mg, Cu 8.30 mg, Fe 23.00 mg, Co 1.20 mg, I 1.00 mg, and Se 0.30 mg. 9 Ethoxyquin; Weifang Jiayijia Bio-tech Co., Ltd., Weifang, China. 10 Henan Jin Yuan Biological Technology Co., Ltd., Zhengzhou, China. 11 Shandong Longxing Biological Engineering Co., Ltd., Jinan, China.…”
Section: Growth Calculationmentioning
confidence: 99%
“…Because of its economic and ecological importance, efforts have been made to improve the productivity of rockfish, including seed production, nutrition regulation, vaccine development, and so on. The recent research on nutritional regulation mainly focuses on dietary macronutrients requirements, especially protein (54.0%, [ 10 ]) and lipid (17.3%, [ 11 ]). In addition, an early study reported that the optimum protein and lipid levels for growth and feed utilization of rockfish fry were 50% and 15%, 45% and 19%, pointing to the obvious protein-sparing effect of lipid [ 12 ].…”
Section: Introductionmentioning
confidence: 99%